Digital Approaches to Manuscript Abbreviations: Where Are We at the Beginning of the 2020s?. Issue 1 (9th July 2021) - Honkapohja, Alpo
Abstract : Abbreviations have been an important qualitative means for dating and localising manuscripts. In digital scholarship, however, they have received less attention. Reasons for this range from digital resources inheriting editorial traditions from print to normalisation being a prerequisite for many research questions. The aim of this paper is to build bridges by giving an overview of scholarship into digital and quantitative approaches – taking into account English, French, Old Norse and, to a lesser extent, Dutch, German and Celtic scholarship. It also makes a theoretical contribution by placing abbreviations into a typology of writing systems and proposing that the terms conditioned and unconditioned variation in analogy with phonology could be useful for studying abbreviation.